2017
DOI: 10.1080/10408398.2017.1342595
|View full text |Cite
|
Sign up to set email alerts
|

Modeling food matrix effects on chemical reactivity: Challenges and perspectives

Abstract: The same chemical reaction may be different in terms of its position of the equilibrium (i.e., thermodynamics) and its kinetics when studied in different foods. The diversity in the chemical composition of food and in its structural organization at macro-, meso-, and microscopic levels, that is, the food matrix, is responsible for this difference. In this viewpoint paper, the multiple, and interconnected ways the food matrix can affect chemical reactivity are summarized. Moreover, mechanistic and empirical app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 75 publications
1
38
0
Order By: Relevance
“…Markowski et al () reported that different varieties of carrots with the same dimensions responded differently during drying treatments causing a variation in drying characteristics. The differences are due to divergence in the varieties, food matrix, structure, tissue, and chemical composition within the crop as explained further by Capuano, Oliviero, and van Boekel (). The authors explained in detail that all the variations will generate different levels of chemical reactions within the food matrix when subjected to thermal treatments, such as drying, which consequently may influence the drying behavior due to changes in thermal properties.…”
Section: Resultsmentioning
confidence: 96%
“…Markowski et al () reported that different varieties of carrots with the same dimensions responded differently during drying treatments causing a variation in drying characteristics. The differences are due to divergence in the varieties, food matrix, structure, tissue, and chemical composition within the crop as explained further by Capuano, Oliviero, and van Boekel (). The authors explained in detail that all the variations will generate different levels of chemical reactions within the food matrix when subjected to thermal treatments, such as drying, which consequently may influence the drying behavior due to changes in thermal properties.…”
Section: Resultsmentioning
confidence: 96%
“…Variability in losses during thermal processing may be due to the differences in food composition, the presence of metal cations, pH, residual headspace in the package or dissolved oxygen content in the food. Capuano et al () reported that factors such as different tissue structure, mechanical damage during harvesting, intrinsic enzyme (ascorbate oxidase) and sulfhydryl group content, and the presence of metal ions, such as Fe 3+ and Cu 2+ can affect the thermal stability of vitamin C in various foods. Herbig and Renard () observed a slightly higher stability of vitamin C and a lower degradation rate in carrot puree at pH 5.5 than for apple puree serum at pH 3.5 when heated at 80 °C for several hours.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin C, also known as L-ascorbic acid, cannot be endogenously synthesized in human body, and is an essential dietary component that is necessary for many biological and physiological functions (Capuano, Oliviero, & van Boekel, 2018). However, it is the most labile vitamin, and is highly susceptible to oxidation.…”
mentioning
confidence: 99%
“…It is expected that protein hydrolysates, as a mixture of defined peptides, would not suffer further modifications, since the linear sequences are affected by sequence decomposition processes, such as hydrolysis itself or fermentation. The heterogeneous chemical composition of a food, as well as its molecular structure, is related to different chemical reaction behaviors [215] and, in consequence, its functionality.…”
Section: Stability and Functionality In Food Matricesmentioning
confidence: 99%